Teoría del derecho y pluralismo jurídico - Vladimir Llano, Jairo (2023)
This article analyzes one of the most important debates in contemporary legal science. On the one hand, some authors consider the law of the state as modernity’s only true source of legal norms. These thinkers base their point of view on a traditional p ositivist theory that presents legislation as the main source of law. On the other hand, there are those who consider state law as one of many sources of rules that may be applied in conflict resolution. These theorists point out how, at the beginning of t he century, local rules, which include sources as diverse as indigenous norms and the norms used by urban communities, became more important. Without denying the significance of transnational and international law, these thinkers underscore the social orig in of law and they put forth the concept of legal pluralism, a key figure in understanding the phenomenon of globalization